Key technologies and research progresses in cognitive SWIPT - Xiaorong XU; Minghang SUN; Linhui SHEN; Yingbiao YAO; Wei FENG (Dianxin kexue)
The combination of cognitive radio (CR) and simultaneous wireless information and power transfer (SWIPT) has become one of the research hotspots in modern high-efficient cognitive radio communications.Firstly,the introduction of SWIPT and cognitive SWIPT were illustrated.Secondly,two types of receiver structures commonly used in SWIPT networks were introduced and the corresponding energy harvesting formulas were given.Thirdly,system model of cognitive SWIPT network and the research progresses of cognitive SWIPT combined with cooperative relaying and MIMO were presented respectively.Future research prospects of the key technologies in cognitive SWIPT network were investigated.Finally,some recent research achievements of the key technologies in cognitive SWIPT were given.Certain referencing values in the theoretical research and future practical applications of high energy-efficient secure cognitive SWIPT communication network were provided.